Milk production profile of Barela camel (Camelus dromedarius) supplemented with postbiotics in a semi-intensive management system: pilot study - Faraz, Asim; Buzdar, Hassan Qadir; Waheed, Abdul; Hussain, Syeda Maryam; Rahman, Sajjad Ur; Bashir, Muhammad Mukarram; Padalino, Barbara (Frontiers in Veterinary Science, 2025)
This pilot study investigated the effects of postbiotics supplementation on both milk yield and composition within a semi-intensive management system in Barela camels. The key indicators included daily milk yield, fats, protein, solid not fats, and lactose levels. A total of 12 dairy camels from early to mid-lactation stages (second to fourth parity) were divided into four groups to obtain similar milk production among groups. Prior to the study, all camels were dewormed and confirmed for good health status. The first group served as the control and was permitted to graze for only 8 h per day without any supplementation. The second group received an additional 3 kg of concentrate feed alongside the same grazing schedule. The third and fourth groups were supplemented with 3 kg of concentrate feed plus 6 grams and 15 grams of extra pure metabolites (postbiotics - XPM), respectively, while maintaining the daily grazing duration of 8 h. The trial spanned 45 days, with an initial adaptation period of 15 days. Milk yield was recorded at four intervals: days 0, 16, 30, and 45. Milk composition analysis occurred on days 0 and 45 to establish baseline and final metrics. A complete randomized design was used, and one-way ANOVA was applied for statistical analysis at a significance level of 5%. The least significant difference test facilitated comparisons among treatment means. Results indicated significant differences in milk production across groups (p < 0.005), with the highest yield observed in the fourth group (8.93 ± 0.74 kg) compared to the control group (4.64 ± 0.32 kg) (p = 0.0010). In terms of milk composition, there was a notable effect on fat percentage among treatment groups, with the fourth group exhibiting the highest fat content (3.40 ± 0.05%) and the control group showing the lowest (2.82 ± 0.05%) (p = 0.0450). However, variations in protein, lactose, and solids-not-fat levels were not statistically significant. In short, postbiotics significantly enhance fat content in Barela dromedary camels, highlighting their potential as a valuable dairy breed within semi-intensive management systems. This will serve as a pilot study for the field of camel science, which could be used for further detailed studies about camel semi-intensive and intensive feeding management systems.